Breaking one barrier at a time: how women developers cope in a men-dominated industry - Canedo, Edna; Mendes, Fabiana; Cerqueira, Anderson; Okimoto, Marcio; Pinto, Gustavo; Bonifacio, Rodrigo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2021)
Context: Participation of women in software development teams is surrounded by several challenges — including gender bias, the difficulty of engagement, and general acceptance of the teams. Objective: We investigated the women perception in relation to interactions, contributions, gender bias, barriers and challenges that they may face in their work. Method: To achieve this goal, we conducted semi-structured interviews with 17 Brazilian women. We analyzed the data using the principles of Grounded Theory and identified three categories: Challenges, Barriers and Gender Issues. Results: Our findings reveal that tasks considered more complex are allocated to men on the team. Our respondents also commonly observe gender bias from men on the team. Conclusions: The findings indicate that most of the interviewed women observe a sexist behavior amongst the software development team members. Moreover, most of the participants stated that few women perform a leadership role in their team. We close by presenting suggestions to more inclusive work environments.